Pelatihan Peningkatan Kualitas Sumber Daya Manusia Bagi UMKM - Sari Wulandari; Suhaila Husna Samosir; Horia Siregar; Melisa Zuriani Hasibuan; Mhd.Dani Habra; Mutawaqil Bilah Tumanggor (LPPI UMN AL WASHLIYAH, 2025)
The government is promoting a revival program for Micro, Small and Medium Enterprises (MSMEs). In this context, MSMEs are required to improve the quality of their human resources. The objective of this community service program is to improve the quality of human resources at Puri Aren Cair. The methods used in The role of MSMEs in the Indonesian economy is not only as a job creator, as evidenced by the percentage reaching 90% compared to large businesses, but MSMEs are also capable of introducing various local products to the international world. Human resource development (HRD) is an important element for the development and sustainability of a company, because without good HRD, company performance can be less than optimal and ultimately affect sales. There are various aspects that need to be considered to build the quality of human resources in order for small industries to be more successful.